عصر حاضر میں سیرت نبوی ﷺ کی روشنی میں بیوی کے حقوق - Zia-Ul-Mustafa Makki Al-Azhari; Ata Ul Mustafa (Mujalla Islami Fikr-o-Tahzeeb (MIFT) / مجلہ اسلامی فکر و تہذیب, 2024)
The relation between husband and wife sustains and generates love, kindness, mercy, compassion and self-sacrifice. Husband and wife, particularly as father and mother, are two significant pillar upon whom the structure of the family rests. Allah Almighty declares some rights of wives and husbands upon each other which they have to fulfill for living a happy life. In this article, we will elaborate some rights of the wife according to Qur'an and particularly, in the light of life of the Holy Prophet (P.B.U.H). The rights of a wife regarding marriage, alimony, dower maintenance, divorce, inheritance etc. have been guaranteed by Islam. The wife is a responsibility that a Muslim must never neglect. In this matter, like in all others, the Holy Prophet (P.B.U.H) is an excellent example for all husbands. The article focuses on the beautiful aspects of His way of dealing with His wives, such as the Holy Prophet's kindness on them, the way He relaxed and had fun with them and justice exhibited in His interactions with His wives.